Evaluation of different mechanical, chemical and physical treatments on breaking dormancy of seed Prickly scorpions (Scorpiurus muricatus L) - ahmad zare; amin lotfi JALALABADI (علوم و فناوری بذر ایران, 2022)
In order to investigate the effect of different treatments on dormancy breaking of Prickly scorpions weed (Scorpiurus muricatus L), three separate experiments were conducted in 2021 at Agricultural Sciences and Natural Resources University of Khuzestan with four replications. experimental treatments consisted of immersion in boiling water (0, 30, 60, 90, 120, 180 seconds), immersion in sulfuric acid (0, 10, 20, 30, 40, 50, 60 and 70 minutes), scarification and soaking (with scarification+ with soaking, with scarification + non soaking, without scarification +with soaking and without scarification and without soaking). The results of boiling water indicated that with increasing soaking time, germination percentage decreased and the highest germination percentage was observed in 30 seconds (85%). under sulfuric acid application conditions, 34% of seeds germinated in 10 minutes and at other times (20 -70 minutes) maximum germination was observed. The highest germination rate in sulfuric acid treatment was predicted to be 52 minutes. The results of scarification and soaking treatments showed that scarification alone led to an increase in germination percentage (92%) and germination decreased to 56% in soaking conditions with scarification. Immersing seeds in sulfuric acid for 50 minutes, application boiling water for 30 seconds and scarification as a solution to braking dormancy of Prickly can be recommended.